The Art and Science of Acoustic Recording: Re-enacting Arthur Nikisch and the Berlin Philharmonic Orchestra's landmark 1913 recording of Beethoven's Fifth Symphony. Issue 3 (2015) - , Aleks Kolkowski; Miller, Duncan; Blier-Carruthers, Amy
No abstract available